Characteristics of Temporal and Spatial evolution of laser-induced plasma under different laser repetition rate. (1st May 2023) - Fu, Xiaoqing; Liang, Fangyuan; Wang, Jingge; Wang, Hui; Dai, Bo
Abstract: To explore the influence of the laser repetition rate on the characteristics of laser-induced plasma, the spatial and temporal evolution characteristics of the plasma generated from a copper alloy sample were compared when the laser repetition rate was varied from 1 to 20 Hz. The intensity and signal-to-back ratio (SBR) of atomic lines gradually increased with increasing laser repetition rate, reached the maximum at 10 Hz, and then decreased, whereas the intensity and SBR of ionic lines continually increased as the laser repetition rate increased. The morphology of the two-dimensional spatial distribution of the spectral line intensity changed from flat to elongate as the laser repetition rate increased. The plasma emission extended over a longer distance. The changes in the temporal and spatial evolution of the plasma temperature with the laser repetition rate were consistent with those of the ionic line intensity. The results indicate that a greater ablation amount of the sample material and a larger high-temperature region in the plasma were formed when the sample was ablated at a higher laser repetition rate. At this time, the heat accumulation in the sample and the confinement effect of the ablation crater on the plasma intensified the collision of particles inside the plasma, forming plasma with a higher degree of ionisation.